Contextual Cell Death in Adaptive Immunity: Selecting a Winning Response - Herbert, Alan (Frontiers in Immunology, 2019)
Winning the game “Rock, Scissors, Paper” depends on what others do. There is no guarantee that one choice will always win. Does the adaptive immune system use the same intransitive logic to select winners? Here I propose that specialized receptor-ligand pairs, called clicks, initiate contextual cell death to select the best adaptive immune response to a particular challenge. The outcome depends heavily on the phenotypic plasticity of the immune system and upon cell assemblies built from different lineages. These assemblies are self-organizing and use clicks to determine the combination of cells best equipped to defeat a threat. The arrangement is highly adaptive and capable of rapid evolution. Opportunities exist to re-engineer click-based assemblies to produce novel therapeutics.